Pemanfaatan Virtual Reality Untuk Meningkatkan Kemampuan Bersosialisasi Pada Klien Skizofrenia: Literature Review - Fadllah, Ellya -; Merduaty, Rona Cahyantari; Hariyati, Rr. Tutik Sri (REAL in Nursing Journal, 2019)
Social dysfunction is a manifestation of symptoms of schizophrenia which is characterized by decreased social functioning. One of the modality therapies that can be done to improve the socialization ability is social skills interventions in the form of repeatedly and gradually socialization exercises in patients. This article aimed to explore the using virtual reality for improving social skills of  patients with  schizophrenia. Literature review used in this study reviewed journals collected  from  Clinical Key, EBSCO, ProQuest and  Scopus since 2007-2019. Literature study in this scientific paper shows the result that using virtual reality in schizophrenia  patient need to  be  applied  to  improve his/her social skills, though the method that already done in conventional way. Virtual reality   is   one   of   methodes   that can be used  to improve social skills of schizophrenia patients. Keyword: Social Skills, Virtual Reality, Schizoprenia